The Effect of Pretreatment With Different Concentrations of Palm Tree Vinegar on The Gelatin Characteristics of Waste Fish Scales - Landukura, Stevin Eben Haezer; Henggu, Krisman Umbu (Jurnal Kelautan dan Perikanan Terapan (JKPT), 2023)
Fish scales have a fairly high protein content, one of which is collagen. Therefore, it is necessary to conduct research related to the use of fish scales as gelatine, which is one of the collagen derivative products. This study used a completely randomized design consisting of 5 treatments of vinegar concentration, namely 10% palm vinegar immersion, 20%, 30%, 40%, 50%. The results showed that the protein content of gelatin from fish scales ranged from 39.95–47.35%, with the lowest protein content in the 10% lontar vinegar treatment, which was 39.95, while the highest protein content was at the 40% lontar vinegar concentration, which reached 47.35%. The average ash content of fish scale gelatin produced in this study was in the range of 46.58%–50.20%, with the lowest ash content found in the 50% palm vinegar pre-treatment, which was 46.58%. On the other hand, the highest ash content was at 30% vinegar concentration, which reached 50.2%. The results of functional group analysis showed that there was absorption of amide A, amide I, amide II, and amide III groups, indicating that the resulting product was gelatin. The most optimal treatment of palm vinegar concentration in this study was found at 40% palm vinegar concentration, namely 48.11% ash content and 47.35% protein, although the protein content did not meet commercial gelatin standards.